Forskning og utvikling i kulturskolefeltet IRIS - den doble regnbuen - Sagmo Aglen, Gry (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
What is going on in Kulturskolen - the Norwegian municipal school of music and performing arts? And what is the relation between the activities in the practice field and research? Kulturskolen is a type of school dependent on cooperation with others - kindergardens, primary and secondary schools, voluntary and professional cultural life, higher education and nonprofit organizations. The field of research related to Kulturskolen is similarly diverse; including both educational research, artistic research and organizational research. This anthology is the result of IRISforsk, a research group linked to the development project for kulturskole named IRIS. The IRIS-project was executed in collaboration between The Norwegian Council for Schools of Music and Performing Art and The Savings Bank Foundation DNB/Dextra Musica, and ran from 2014 to 2016. The anthology includes 13 chapters, eight of which are scientific papers evaluated by external peer-review. Contributors in the anthology are affiliated with five different educational institutions. The chapters discuss and visualize the scope of music and art school related research, including didactics, professional-oriented and management-focused issues, as well as organizational cooperation, talent development and culture as a tool for inclusion. The anthology targets anyone with an interest in research and development in the music and art school related field - researchers, staff and students in artistic education, teacher education and management education, as well as teachers, managers and other practitioners in the field.